UPAYA HUKUM TERHADAP BENDA-BENDA BERGERAK DALAM HAL PERTANGGUNGAN KEBAKARAN BERDASARKAN KITAB UNDANG-UNDANG HUKUM DAGANG (KUHD) - Ary Diantara, I Made; Dirksen, A. A. Ngr. Gede (Kertha Semaya : Journal Ilmu Hukum, 2013)
Fire insurance related to moving things are ruled in article 295, clause 1commercial code. Generally, this article rules about the verification of thing valueestimate which was responsible for both of each side. About the disadvantages got bythe insurer for moving things saved in the buildings, warehouses, etc. According toarticle 295, clause 2 should be counted by the objects price when the fire had happened.In this paper will be explained about one main problem related to how theimplementation of law effort to moving things in the fire insurance based on commercialcode. The method, that article i use yuridis normatif and the conclusion of this article isbased on commercial code, that the verification of the insurance by in surance party,the cost was adapted by the interpretation of value.
Keywords: Insurance, Fire, Law Effort, Moving Things